The Effect of the Covid-19 Pandemic on Increased Anxiety of Cancer Survivors of Wijayakusuma Group - Prima, Ian Oscar; Darwito (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Corona Virus Disease-19 (COVID-19) is an infectious disease caused by the SARS-CoV2 virus. The increasing number of COVID-19 cases have caused anxiety problems in several countries. Breast cancer patients already have anxiety about their own disease. During the COVID-19 pandemic, this anxiety might be increased due to the fear of getting infected both in the environment where they live or in the hospital. Methods. This is a descriptive observative study, on females with history of cancer in the Wijayakusuma group, Dr. Kariadi Hospital, Semarang, Central Java during February – March 2021. Data collected using questionnaire based on Generalized Anxiety Disorder 7-item (GAD-7) that the question was modified for evaluating anxiety about COVID-19 pandemic in breast cancer patients. Data analyzed using SPSS 23rd version Results. In this study, the breast cancer patient who not anxious were 19.1%, slightly anxious 35.5%, moderate anxious 23.6%, and severe anxious 21.8%. 74,5% patients feel they must wash their hands more often. 60,9% were worried about possibility of contracting COVID-19 of their members, 49,1% afraid of COVID-19, 50,9% were not afraid about COVID-19, 44,5% feel uncomfortable when think about COVID-19, and 40,9% Feel that COVID-19 is life-threatening. Conclusion. There was increase of anxiety level. There was a behavioral change in patients where patients wash their hands more often due to the COVID-19 pandemic.